Efektivitas Komik Edukasi terhadap Upaya Pencegahan Kekerasan pada Anak Sekolah Dasar Negeri Penggilingan 09 Pagi Jakarta Timur Tahun 2019 - Triana Indrayani; Nadya Namira (Lembaga Penelitian Universitas YARSI, 2020)
Comics are effective in increasing elementary school children's knowledge because comics have attractive colors and images, therefore they can facilitate easy understanding of a concept. One group of children who are vulnerable to being victims of sexual violence were elementary school children. This study aimed to measure the effectiveness of educational comics on the prevention of violence in elementary school children. The research design used in this study was a pre-experimental using the One Group Pre-Post-Test design, the sample in this study was 32 students taken using total sampling. The instrument used was a questionnaire, the data analysis used paired t test. The results showed that there were significant differences in the pretest and posttest after the educational comic intervention. There is a significant influence between the effectiveness of educational comics on prevention of violence in state elementary School Children before the intervention and after the intervention. It is expected that students will be more proactive in finding information about preventing violence in children so that they can apply the information obtained as well as possible.